1993
DOI: 10.1007/bf01309661
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a C-type retrovirus from an HIV infected cell line

Abstract: A study by electron microscopy of HUT 78 cells infected with the ARV-2 strain of HIV-1 revealed, in addition to virions having the characteristic morphology of a lentivirus, the presence of numerous C-type particles, suggesting that the analysed specimen might in fact contain two different viruses. In order to further investigate this observation, the cell culture supernatant was filtered and mixed at serial dilutions with uninfected HUT 78 cells. In this way, it was possible to obtain cells producing only vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The broad in vitro host range of GALV, its apparently well-conserved receptor (42), and the evidence presented for taxonomic cross-transmission in vivo suggest that the members of the GALV-KoRV group have the potential for future host jumping. Furthermore, simian type C-related virus sequences and cross-reactive proteins have been detected in humans (14,17,20,31), and a novel strain of GALV (GALVX) has been isolated from a human cell line (5,43). Continuing studies are aimed at further defining the epizootiology of the KoRV-GALV group and at clarifying the pathogenic and zoonotic potential of this virus.…”
Section: Discussionmentioning
confidence: 99%
“…The broad in vitro host range of GALV, its apparently well-conserved receptor (42), and the evidence presented for taxonomic cross-transmission in vivo suggest that the members of the GALV-KoRV group have the potential for future host jumping. Furthermore, simian type C-related virus sequences and cross-reactive proteins have been detected in humans (14,17,20,31), and a novel strain of GALV (GALVX) has been isolated from a human cell line (5,43). Continuing studies are aimed at further defining the epizootiology of the KoRV-GALV group and at clarifying the pathogenic and zoonotic potential of this virus.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the infected woolly monkey had close contact with an infected gibbon [22]. In addition to these strains, related GALV were isolated from a GALV-SSAV infected marmoset tumor cell line, designated GALV-MAR (Accession number U20589.1) and from an HIV-1-infected human cell line (GaLV-X) [28,29], revealing laboratory contaminations similar to the situation with the xenotropic murine leukaemia virus (MuLV)-related virus (XMRV) in human tissues [30]. …”
Section: The Gibbon Ape Leukaemia Virus (Galv)mentioning
confidence: 99%
“…A further unusual feature of KoRV is the close genetic relationship it shares with gibbon ape leukemia virus (GALV), an exogenous virus initially isolated from captive white-handed gibbons ( Hylobates lar ) in Thailand with malignant lymphoma and leukemia, and later isolated from other gibbons with lymphoid tumours, gibbons inoculated with human material or as a human cell culture contaminant [19]–[22]. KoRV and GALV share a high degree of homology across the entire viral genome and both viruses form a clade with eutherian (porcine, murine, feline and chiropteran) gammaretroviruses [11], [23].…”
Section: Introductionmentioning
confidence: 99%